2017
DOI: 10.1111/voxs.12344
|View full text |Cite
|
Sign up to set email alerts
|

Keys to move to self‐sufficiency in safe blood components based on voluntary blood donation

Abstract: One of the oldest resolutions of WHO urges member states to promote the blood services based on voluntary non‐remunerated blood donation (VNRBD). Consequently, achieving self‐sufficiency in six driver products has been focused on by the WHO and other international agencies in 2010. However, both VNRBD and self‐sufficiency are not a reality in many countries. In this article, proposed ways to achieve self‐sufficiency in blood products and plasma‐derived medicines are discussed. The main proposed ways included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Studies that previously argued that replacement donors carry a higher rate of TTI compared with VNRDs have been reevaluated and shown to have significant methodologic flaws, including confounding between first-time and repeat donors. 29 , 87 89 First-time donors do have a higher rate of TTI than recurrent donors, and the studies that showed a higher rate of TTI in replacement donors never controlled for the higher rate of first-time donors in the replacement pool. One ground-up alternative incorporates elements of both.…”
Section: Challenges To the Blood Transfusion Process In Low-resource Settingsmentioning
confidence: 99%
“…Studies that previously argued that replacement donors carry a higher rate of TTI compared with VNRDs have been reevaluated and shown to have significant methodologic flaws, including confounding between first-time and repeat donors. 29 , 87 89 First-time donors do have a higher rate of TTI than recurrent donors, and the studies that showed a higher rate of TTI in replacement donors never controlled for the higher rate of first-time donors in the replacement pool. One ground-up alternative incorporates elements of both.…”
Section: Challenges To the Blood Transfusion Process In Low-resource Settingsmentioning
confidence: 99%
“…Annually, over 2,100,000 whole blood units are collected in Iran (13). According to a study from Iran performed in 2013, over one-quarter of prospective blood donors were deferred due to donor or recipient safety (14).…”
Section: Introductionmentioning
confidence: 99%